Plutocracy, bureaucracy and the end of public trust - Green, Richard T. (2012)
This contribution/invitation to Disputatio critically examines the failures of governance in the American financial system that contributed to the financial and economic crisis of 2007-2008 and the ensuing "Great Recession" that has yet to abate. The public administration has played a significant role in this disaster, and yet as a field we have given it far too little attention. There are many important lessons to learn about it, especially concerning managerial ideology and how this has contributed to the failure of governance in the financial system. The analysis here draws heavily from two recent government reports and a burgeoning literature (mostly from other fields) on the subject. The "Final Report of the National Commission on the Causes of the Financial and Economic Crisis in the United States" and a U.S. Senate report titled "Wall Street and the Financial Crisis: Anatomy of a Financial Collapse" present lucid accounts with extensive documentation of the nature and causes of the crisis. It is a complex story worth exploring in some detail for the sake of understanding how things went so terribly wrong in a system so vital to the livelihood of a nation and its millions of inhabitants.- Reproduced.
Keywords: Economic recession